SINTESIS BIO-OIL DARI BONGGOL JAGUNG MENGGUNAKAN PROSES PIROLISIS - Cakradetha, Ivenda Sasquea; Suriyanto, Suriyanto; Santi, Sintha Soraya; Utami, Isni; Sutiyono, Sutiyono (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Bio-Oil is a raw material that can be produced through various methods, one of which is the biomass pyrolysis process. Biomass pyrolysis has been extensively studied and has shown promising potential as an alternative fuel due to its lignocellulose content. In Indonesia, corn production reaches 23.1 million tons, resulting in waste in the form of corn cobs. This study employed the fast pyrolysis method to convert corn cobs into Bio-Oil. The pyrolysis process was conducted in a sealed reactor, externally heated to a temperature of 400°C. The corn cobs used as raw material were first crushed and sieved to achieve a uniform particle size of 20 mesh. Subsequently, the corn cobs were placed into the pyrolysis reactor, with residence times varied at 40, 60, 80, 100, and 120 minutes. Upon completion of the pyrolysis process, the resulting products, consisting of Bio-Oil, charcoal, and pyrolysis gas, were separated and analyzed for Bio-Oil yield, density, viscosity, and calorific value. Chemical composition analysis was performed using Gas Chromatography-Mass Spectrometry (GC-MS) to identify the main compounds present in the Bio-Oil. The highest yield was obtained with a particle size of 20 mesh and a residence time of 120 minutes, resulting in a yield of 72.4632%, a density of 1.3018 kg/m³, a viscosity of 1.6712 mm²/s, and a calorific value of 6.640 Kcal/kg. GC-MS analysis revealed an acetic acid content of 37.49% and a methyl ester content of 22.19%.